Forming Ideal Leader for Youth in the Future in the Challenging Globalization through Al-Ghazali’s Islamic Character Education - Satiul Komariah; Slamet Setioboro (Proceeding of International Conference on Islamic Education, 2016)
In Islam, leader has been exemplified by Prophet Muhammad, but many of today leaders are far away from the examples provided by him. They ignore the most important essences of being a good leader. Finally, they are not ready to face the globalization. Abū Hamid Muhammad ibn Muhammad ibn Muhammad al-Ghazali Tusi al Safi'i, known as al-Ghazali was a hujjah or writer of Islam (1058-1111 AD) with the concept of deeper thought leaders emphasizes the substantial aspects of the religion values than in terms of formal-symbolic, uniting what has been ommited from the leader; the concept of democracy. There are three formulation to achieve an ideal leader following al-Ghazali; first, the concept of an ideal leader according al-Ghazāli, second, the type of thought leadership of al-Ghazali. third, the relevance of the thought of al-Ghazali in the field of character education for the young generation as potentials for the ideal future leaders. This research employs library research method. The research found that the type of ideal leader according to al-Ghazali is the leader of morals; of fair-ness, and has integrity, competence, mastery in the field of state and religion. Intellect, religion, and morality have a great influence and role. These are expected to be able to prevent the destruction and damage within a nation and makes the society prosperous with a moral that supported religion as its foundation. Finally, they have enough provisions to face the globalization.